MATRIX TRANSFORMATIONS OF c0(p,s), 100(p,s) and l(p,s) INTO Q - Et, Mikail; Başarır, Metin (My University, 1997)
Necessarv and sufficicnt condi,tions haYe been cstablished for an infini te matrix A= (?k) to transform c0(p,s) , f.00(p,s) and ((p,s) into Q (semipcriodic scqucnces space), \\vhere c 0(ps) and e00( p,s) the set of aJJ complex sequenccs X= (xk) such that limk (k-slxkıPk)=O and supk (k-slxkı Pk)respectively., p = (PJç) strictly positive nunıbcrs anJ s> O is a real number,
Keywords: Matematik